IMPROVING ADVANCE CARE PLANNING UPTAKE IN GENERAL INTERNAL MEDICINE THROUGH SYSTEM-LEVEL INTERVENTIONS - Ali Muteb Almutairi¹, Nasser Mohammed Aldhafiri¹, Yousif Ali Abdullah Aldhafeeri¹, Sultan Salman Aldhafeeri¹, Tariq Hulayyil Alanazi², Majed Mohammed Sfah Alshammry³, Dr. Khalid Obaid Alanazi4 (Chelonian Research Foundation, 2022)
Advance care planning (ACP) is a process that enables individuals to make decisions about their future healthcare, particularly end-of-life care, in the event that they lose the capacity to make or communicate these decisions. Despite the numerous benefits of ACP, uptake remains low in general internal medicine settings. This study aimed to investigate the effectiveness of system-level interventions in improving ACP uptake among patients in a general internal medicine department. A quasi-experimental design was employed, with a sample of 200 patients recruited from the internal medicine department of a tertiary hospital in Saudi Arabia. The intervention consisted of a multi-component program, including healthcare provider education, patient education, and the integration of ACP into the electronic medical record system. Data were collected using a structured questionnaire and medical record review at baseline and three months post-intervention. The primary outcome measure was the proportion of patients who completed an advance directive. Secondary outcomes included patients' knowledge and attitudes towards ACP, healthcare providers' knowledge and attitudes towards ACP, and the quality of ACP discussions. Data were analyzed using descriptive statistics, McNemar's test, and logistic regression analysis. The results showed a significant increase in the proportion of patients who completed an advance directive from 10% at baseline to 35% post-intervention (p < 0.001). Patients' knowledge and attitudes towards ACP also improved significantly (p < 0.001), as did healthcare providers' knowledge and attitudes (p < 0.001). The quality of ACP discussions, as measured by the ACP Discussion Quality Checklist, improved from a mean score of 2.5 (SD = 1.2) at baseline to 4.2 (SD = 0.8) post-intervention (p < 0.001). Logistic regression analysis identified patient education (OR = 2.45, 95% CI: 1.32-4.56) and healthcare provider education (OR = 1.88, 95% CI: 1.02-3.48) as significant predictors of advance directive completion. The findings suggest that system-level interventions, particularly patient and healthcare provider education, can effectively improve ACP uptake in general internal medicine settings. Recommendations for practice and future research are discussed. Keywords: advance care planning, advance directives, end-of-life care, general internal medicine, system-level interventions